2019
DOI: 10.1029/2018ja026353
|View full text |Cite
|
Sign up to set email alerts
|

On the Relationship Between the Rate of Change of Total Electron Content Index (ROTI), Irregularity Strength (CkL), and the Scintillation Index (S4)

Abstract: We present a new quantitative theory for the rate of change of total electron content index (ROTI) by noting its straightforward relationship to the phase structure function of ionospheric turbulence. The theory provides the dependence of ROTI on the sampling interval, satellite motion, propagation geometry, and the spectral shape, strength, anisotropy, and drift of the irregularities. We also present useful approximations to the full theory that elucidate the principal dependencies. We show, for example, that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
42
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 20 publications
3
42
1
Order By: Relevance
“…Correlation between SNR 4 and TEC does exists from cases of measured amplitude scintillation. The latter observation is also expected as several studies demonstrated correlation and casual relationship between ROTI and S 4 (Carrano et al, 2019;Liu & Radicella, 2019;Yang & Liu, 2016). Correlation deviation in this formalism is thought to be due to viewing geometry and irregularity drift velocity (Carrano et al, 2019;Liu & Radicella, 2019).…”
Section: 1029/2020rs007131supporting
confidence: 65%
“…Correlation between SNR 4 and TEC does exists from cases of measured amplitude scintillation. The latter observation is also expected as several studies demonstrated correlation and casual relationship between ROTI and S 4 (Carrano et al, 2019;Liu & Radicella, 2019;Yang & Liu, 2016). Correlation deviation in this formalism is thought to be due to viewing geometry and irregularity drift velocity (Carrano et al, 2019;Liu & Radicella, 2019).…”
Section: 1029/2020rs007131supporting
confidence: 65%
“…The high-rate measurements are not available, however, for all GPS receiver stations, and often various scintillation proxies are used that only require measurements of the total electron content (TEC) at a lower resolution, for example, at 1 Hz. One such proxy is based on the rate of TEC change index (ROTI), and although the relationship between ROTI and traditional scintillation metrics is yet to be established conclusively, some previous studies found significant correlations, particularly with S 4 at low latitudes (Carrano et al, 2019) and with σ ϕ at high latitudes (Prikryl et al, 2013). Despite wider availability…”
mentioning
confidence: 99%
“…Therefore, Acharya and Majumdar [33] gives the conclusion about strong evidence of a relationship between ROTI and S4, which in general agrees with the analysis from this study. In addition, Carrano et al [31] also demonstrated the theoretical relationship between ROTI and S4 and has demonstrated that this relationship is highly dependent on the sampling rate. They also provide reasons why this relationship varies between different dates and in different regions.…”
Section: Discussionmentioning
confidence: 96%
“…The relationship between ROTI and scintillation has been investigated [9,11,[31][32][33]. The scatter plot and the time series plot are common methods used in recent studies to demonstrate the linear relationship between ROTI, S4 and σ ϕ [9,11,31,32]. Additionally, the relationship between ROTI and scintillation has been shown to be affected by changes in elevation angle [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation